ELECTRIC-FIELD EFFECTS ON ZERO-KINETIC-ENERGY PHOTOELECTRON-SPECTRA - AN EXPLANATION OF OBSERVED TRENDS - Merkt, F; Fielding, H; Softley, T (1993)
An explanation is offered for the propensity for large negative changes of rotational angular momentum in ZEKE photoelectron spectra, which is increasingly observed as the rotational constant of the photoion decreases; Stark mixing becomes progressively more important, facilitating multistep rotational autoionization processes. The Inglis-Teller limit serves as a useful benchmark for assessing the importance of electric field effects. A discussion is presented of the relative importance of l mixing and J mixing. © 1993.